2006
DOI: 10.1073/pnas.0510836103
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the norepinephrine transporter gene alters promoter activity and is associated with attention-deficit hyperactivity disorder

Abstract: The norepinephrine transporter critically regulates both neurotransmission and homeostasis of norepinephrine in the nervous system. In this study, we report a previously uncharacterized and common A/T polymorphism at ؊3081 upstream of the transcription initiation site of the human norepinephrine transporter gene [solute carrier family 6, member 2 (SLC6A2)]. Using both homologous and heterologous promoter-reporter constructs, we found that the ؊3081(T) allele significantly decreases promoter function compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 30 publications
(40 reference statements)
3
136
2
1
Order By: Relevance
“…39 Recently, a novel SNP (À3081[A/T]) in the nearby promoter was identified and reported to be modestly associated with ADHD in a set of 94 ADHD cases and 60 controls (P = 0.029). 23 Although this SNP is currently not available in the public database, the location of À3081[A/T] is 3081 bp upstream of the transcription start site and there were no indications that recombination had occurred between rs3785143 and SNPs around this upstream region (D 0 = 1) (Figure 1). So it is also possible that this association may have been due to high LD with rs3785143.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Recently, a novel SNP (À3081[A/T]) in the nearby promoter was identified and reported to be modestly associated with ADHD in a set of 94 ADHD cases and 60 controls (P = 0.029). 23 Although this SNP is currently not available in the public database, the location of À3081[A/T] is 3081 bp upstream of the transcription start site and there were no indications that recombination had occurred between rs3785143 and SNPs around this upstream region (D 0 = 1) (Figure 1). So it is also possible that this association may have been due to high LD with rs3785143.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] Earlier studies investigated only a few genetic markers in NET and found no evidence of association. [18][19][20] Xu et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) Other gene variants also have been suggested to be associated with AD/HD such as genes that encode monoamine oxidase A, dopamine b-hydroxylase, norepinephrine transporter (NET), and a2-adrenoceptor. [10][11][12] It is also thought that the gene-environment interactions exist in the etiology of AD/HD. The most consistent and robustly associated results are prenatal exposure to nicotine from smoking in utero.…”
Section: Human Studies Of Ad/hdmentioning
confidence: 99%
“…Since NE is a fundamental neurochemical messenger, its accurate regulation is of major importance. Thus, the NET, responsible for NE equilibrium in the synaptic cleft, is representing the reuptake site and considered to be involved in a variety of neurological/psychiatric disorders [1,2], but also plays a pivotal role in cardiovascular [1][2][3] and metabolic diseases [3][4][5]. Reduced NET levels go along with neurological disorders like major depression [6,7], Parkinson's disease (PD), Alzheimer's disease (AD) [8][9][10][11][12][13][14][15][16][17][18], and cardiovascular diseases such as hypertension, cardiomyopathy, and heart failure [5,13].…”
Section: Introductionmentioning
confidence: 99%